Molecular signatures of X chromosome inactivation and associations with clinical outcomes in epithelial ovarian cancer. (21st December 2018) - Winham, Stacey J; Larson, Nicholas B; Armasu, Sebastian M; Fogarty, Zachary C; Larson, Melissa C; McCauley, Brian M; Wang, Chen; Lawrenson, Kate; Gayther, Simon; Cunningham, Julie M; Fridley, Brooke L; Goode, Ellen L
Abstract: X chromosome inactivation (XCI) is a key epigenetic gene expression regulatory process, which may play a role in women's cancer. In particular tissues, some genes are known to escape XCI, yet patterns of XCI in ovarian cancer (OC) and their clinical associations are largely unknown. To examine XCI in OC, we integrated germline genotype with tumor copy number, gene expression and DNA methylation information from 99 OC patients. Approximately 10% of genes showed different XCI status (either escaping or being subject to XCI) compared with the studies of other tissues. Many of these genes are known oncogenes or tumor suppressors (e.g. DDX3X, TRAPPC2 and TCEANC ). We also observed strong association between cis promoter DNA methylation and allele-specific expression imbalance ( P  = 2.0 × 10 −10 ). Cluster analyses of the integrated data identified two molecular subgroups of OC patients representing those with regulated ( N  = 47) and dysregulated ( N  = 52) XCI. This XCI cluster membership was associated with expression of X inactive specific transcript ( P  = 0.002), a known driver of XCI, as well as age, grade, stage, tumor histology and extent of residual disease following surgical debulking. Patients with dysregulated XCI ( N  = 52) had shorter time to recurrence (HR = 2.34, P  = 0.001) and overall survival time (HR = 1.87, P  = 0.02) than those with regulated XCI, although results were attenuated after covariate adjustment. Similar findings were observed when restricted to high-grade serous tumors. We found evidence of a unique OC XCI profile, suggesting that XCI may play an important role in OC biology. Additional studies to examine somatic changes with paired tumor-normal tissue are needed.